Pain experience and perception in individuals with Snijders Blok-Campeau syndrome - Ocay, Don Daniel; Campeau, Philippe M.; Berde, Charles B.; Brownstein, Catherine A. (Frontiers in Pain Research, 2025)
IntroductionSnijders Blok-Campeau Syndrome (SNIBCPS) is a neurodevelopmental disorder characterized by intellectual disability, developmental delays, speech impairment, hypotonia, and distinctive facial features. Little is known about pain perception in children with cognitive impairments, such as patients with SNIBCPS. Although it has been noted that some individuals with SNIBCPS have decreased pain sensation and response to painful stimuli, these reports are anecdotal. Therefore, the objective was to better understand this syndrome and the affected individual's perception and response to pain through proxy-reported observational assessments.MethodsFifteen caregivers of individuals with a diagnosis of SNIBCPS participated in this mixed-methods anonymous survey study between July and September 2024. The survey questionnaires included the Pediatric Pain Profile, a Pain Sensory Questionnaire, the Non-Communicative Children's Pain Checklist-Revised, and the Individualized Numerical Rating Scale.ResultsAlmost a quarter of our respondents reported insensitivity in the affected individual to hard impacts or pressure. Our findings highlight early and past painful experiences in individuals with SNIBCPS who have a range of behaviors to express their pain.DiscussionOur findings bring awareness about the proper examination of individuals with SNIBCPS. Despite the small sample size, our findings suggest that pain and injuries may go unreported in individuals with SNIBCPS, and individualized parental observational scales may be beneficial for their healthcare providers and their caregivers.